2007
DOI: 10.1177/0731684407076713
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Beneficial Effects of Interference-fit in Pin-loaded FRP Composites

Abstract: Interference-fit pin connections have wide applications ranging from aerospace structures to electric hardware systems and the telephone industry. In order to derive the maximum benefit by the use of interference-fit pin in all such applications, a complete understanding of their behavior in the regions of joints is essential. This paper deals with the study of various beneficial effects of interference-fit pin-loaded FRP composite laminates. Three-dimensional finite element models have been created to simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…The end of specimen has been fixed on the X and Y-direction by considering mechanical clamping on the experimental set-up. In the analysis, the pin drives the hole toward the bottom surface of the GFRP specimen, and contact area between GFRP and the hole has a friction coefficient of 0.1 to simulate the real situation [13,28]. The total driving distance was set at 10 mm which is enough to penetrate the GFRP specimen, and has been divided into 400 sub-steps with same driving distance at each sub-step.…”
Section: Fe Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…The end of specimen has been fixed on the X and Y-direction by considering mechanical clamping on the experimental set-up. In the analysis, the pin drives the hole toward the bottom surface of the GFRP specimen, and contact area between GFRP and the hole has a friction coefficient of 0.1 to simulate the real situation [13,28]. The total driving distance was set at 10 mm which is enough to penetrate the GFRP specimen, and has been divided into 400 sub-steps with same driving distance at each sub-step.…”
Section: Fe Modelingmentioning
confidence: 99%
“…They reported that FE model required considering frictional contact condition and material nonlinearity to simulate the behavior of the composite joint accurately. Pradhan and Babu [13] performed non-linear contact analysis to study the effects of interference for different material cases. They formulated 3-D FE models to investigate the effects of interference-fits in pin-loaded laminates and considered friction between the pin and the hole surface to simulate the real situation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jiang et al 8,9 have developed a two-dimensional axis-symmetric finite element (FE) model to simulate the interference fit bolt insertion process, and then analyzed the deformation and residual stress distribution around the hole. For interference fit fastened structure subjected to an external load, the studies [10][11][12][13][14][15][16] were sufficient, but they only considered the stress analysis in the loading stage and lacked the simulation in the fastener installation stage. Usually, an even-distributed residual compressive stress was directly given at the beginning of loading in those studies.…”
Section: Introductionmentioning
confidence: 99%